Differential Impact of Education on Gray Matter Volume According to Sex in Cognitively Normal Older Adults: Whole Brain Surface-Based Morphometry - Kang, Dong Woo; Wang, Sheng-Min; Na, Hae-Ran; Kim, Nak-Young; Lim, Hyun Kook; Lee, Chang Uk (Frontiers in Psychiatry, 2021)
Background: The effect of educational status on brain structural measurements depends on demographic and clinical factors in cognitively healthy older adults. Objectives: The current study aimed to evaluate the impact of interaction between years of education and sex on gray matter volume and to investigate whether cortical volume has a differential impact on cognitive function according to sex. Methods: One hundred twenty-one subjects between 60 and 85 years old were included in this study. Gray matter volume was evaluated by whole brain surface-based morphometry. Multiple regression analysis was used to analyze the effects of sex-cortical volume interactions on cognitive functions. Results: There was a significant interaction between years of education and sex on the cortical volume of the left inferior temporal gyrus after adjusting for age, APOE ε4 allele prevalence, and total intracranial volume. In addition, we found a significant impact of the interaction between adjusted left inferior temporal volume and sex on CERAD-K total scores. Conclusion: These findings have significant implications for the understanding of how sex could affect the role of cognitive reserve for cortical atrophy in cognitively intact older adults.